Influence of Tillage Methods and Plant Protection Agents on the Ecological Parameters of Soil Cover and Barley Yield - A. A. Sardar; Zh. S. Tileubaeva (Сельскохозяйственные машины и технологии)
Excessive and unbalanced use of the pesticides that is necessary to protect agrophytocenoses against pests leads to environmental pollution. Harmful pesticides tend to enter the natural cycles of substances. Therefore, they are quick to disappear or be destructed by biological agents. There are also “nondestructive” pesticides, which do not enter the natural cycles; neither they are accumulated in food chains and in biotopes. These substances have become an object of research in the fi eld of environmental safety.